Association of serum 25-hydroxyvitamin D with influenza in case-control study nested in a cohort of Japanese employees. Issue 5 (October 2017) - Nanri, Akiko; Nakamoto, Kengo; Sakamoto, Nobuaki; Imai, Teppei; Akter, Shamima; Nonaka, Daisuke; Mizoue, Tetsuya
Summary: Background & aims: Several intervention studies have examined the effect of vitamin D supplementation on influenza or influenza-like illness, but their results have been inconsistent. We prospectively examined the association of serum 25-hydroxyvitamin D with influenza among Japanese workers. Methods: We conducted a nested case-control study in a cohort of workers in 4 companies in the Kanto and Tokai areas of Japan. Physician-diagnosed influenza that occurred during the winter season was ascertained using a self-administered questionnaire. Two controls matched by company, sex, and age (and checkup date in 1 company) were selected for each case. Serum 25-hydroxyvitamin D concentrations at baseline were measured using a competitive protein binding assay. Odds ratio of influenza were estimated by conditional logistic regression with adjustment for covariates. Results: Of 182 cases and 364 controls, 179 cases and 353 controls with complete data were included in the analysis. Serum 25-hydroxyvitamin D concentrations were not associated with a significantly lower risk of influenza; the multivariable-adjusted odds ratio for the highest (≥30 ng/mL) versus lowest category (<20 ng/mL) was 0.77 (95% confidence interval 0.37–1.59) ( P for trend = 0.80). In a subgroup of participants without vaccination, vitamin D sufficiency (≥30 ng/mL) was associated with a significantly lower risk of influenza (odds ratio 0.14; 95% confidence interval 0.03–0.74). Conclusions: Overall, circulating 25-hydroxyvitamin D concentrations were not appreciably associated with influenza episodes. However, the lower influenza risk associated with vitamin D sufficiency among unvaccinated participants warrants further investigation.